Efektivitas Pemberian Terapi Dzikir Terhadap Penurunan Resiko Self Harm pada Remaja di SMPN 30 Banjarmasin - Melanda, Nila; Rahman, Subhannur; Tasalim, Rian (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Adolescence is characterized by physical and psychological changes that often cause emotional distress, so some adolescents express stress through self-harm behavior. This condition can have an impact on the appearance of shame, depression, and anxiety. This study aims to analyze the effectiveness of dhikr therapy in reducing the risk of self-harm in adolescents at SMPN 30 Banjarmasin. The study used a quantitative method with a pre-experimental one group pretest-posttest design. The sample consisted of 35 respondents who were selected through purposive sampling techniques. Data collection was carried out using the Self-Harm Inventory (SHI) questionnaire and analyzed using the Wilcoxon test. The results showed a significant difference in the level of self-harm before and after dhikr therapy (p=0.00), with all respondents (100%) experiencing a decrease in the level of self-harm to the mild category. These findings prove that dhikr therapy is effective in reducing the risk of self-harm in adolescents. This therapy can be a simple, independent intervention that is beneficial for improving adolescent mental health and emotional control